A systematic review of reliable and valid tools for the measurement of patient participation in healthcare. Issue 2 (28th September 2015) - Phillips, Nicole Margaret; Street, Maryann; Haesler, Emily
Abstract : Introduction: Patient participation in healthcare is recognised internationally as essential for consumer-centric, high-quality healthcare delivery. Its measurement as part of continuous quality improvement requires development of agreed standards and measurable indicators. Aim: This systematic review sought to identify strategies to measure patient participation in healthcare and to report their reliability and validity. In the context of this review, patient participation was constructed as shared decision-making, acknowledging the patient as having critical knowledge regarding their own health and care needs and promoting self-care/autonomy. Methods: Following a comprehensive search, studies reporting reliability or validity of an instrument used in a healthcare setting to measure patient participation, published in English between January 2004 and March 2014 were eligible for inclusion. Results: From an initial search, which identified 1582 studies, 156 studies were retrieved and screened against inclusion criteria. Thirty-three studies reporting 24 patient participation measurement tools met inclusion criteria, and were critically appraised. The majority of studies were descriptive psychometric studies using prospective, cross-sectional designs. Almost all the tools completed by patients, family caregivers, observers or more than one stakeholder focused on aspects of patient–professional communication. Few tools designed for completion by patients or family caregivers provided valid and reliable measures of patient participation. There was low correlation between many of the tools and other measures of patient satisfaction. Conclusion: Few reliable and valid tools for measurement of patient participation in healthcare have been recently developed. Of those reported in this review, the dyadic Observing Patient Involvement in Decision Making (dyadic-OPTION) tool presents the most promise for measuring core components of patient participation. There remains a need for further study into valid, reliable and feasible strategies for measuring patient participation as part of continuous quality improvement.